Turkish banking banking under political instability and chronic high inflation - Altunbas, Yener; Kara, Alper 1977-; Olgu, Özlem 1979- (Palgrave Macmillan studies in banking and financial institutions, 2009)
In light of Turkey's EU bid and the successful IMF-led disinflation program, this book explores the evolution and performance of the Turkish banking sector. Analyzing the repercussions of overall economic structure, financial crises and political instability on its financial sector, it scrutinizes the prospects for the future of banking sectors.